2020
DOI: 10.1007/s00439-020-02221-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut microbiome in graft fibrosis after pediatric liver transplantation

Abstract: Liver transplantation (LT) is a life-saving option for children with end-stage liver disease. However, about 50% of patients develop graft fibrosis in 1 year after LT, with normal liver function. Graft fibrosis may progress to cirrhosis, resulting in graft dysfunction and ultimately the need for re-transplantation. Previous studies have identified various risk factors for the post-LT fibrogenesis, however, to date, neither of the factors seems to fully explain the cause of graft fibrosis. Recently, evidence ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…Imbalances in the intestinal flora and hyperproliferation of these microorganisms can lead to the destruction of the intestinal barrier. Because the intestinal flora flows into the liver through the portal vein (46), disruptions of the intestinal flora lead to immune responses in the liver and aggravated liver fibrosis occurrence and development (47). However, homeostasis of the intestinal flora supports the stability of the immune system (48).…”
Section: The Liver-intestine Axismentioning
confidence: 99%
“…Imbalances in the intestinal flora and hyperproliferation of these microorganisms can lead to the destruction of the intestinal barrier. Because the intestinal flora flows into the liver through the portal vein (46), disruptions of the intestinal flora lead to immune responses in the liver and aggravated liver fibrosis occurrence and development (47). However, homeostasis of the intestinal flora supports the stability of the immune system (48).…”
Section: The Liver-intestine Axismentioning
confidence: 99%
“…Various liver diseases, including alcoholic liver disease, nonalcoholic liver disease, and primary sclerosing cholangitis, are associated with an altered microbiome ( Tilg et al., 2016 ). Furthermore, studies have shown that dysbiosis can increase toxic metabolites, cause liver inflammation and damage, aggravate liver disease, promote disease progression to liver fibrosis, and seriously affect patient outcomes ( Beraza, 2019 ; Zhou et al., 2019 ; Qin et al., 2021 ). These studies have predominantly focused on advanced liver fibrosis; however, there are few studies that have analyzed changes in the gut microbiota in the early stages of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The imbalanced BA metabolism increases intestinal permeability or decreases the production of SCFAs via the bridging function of the gut-liver axis, altering the gut microbiome composition and stimulating fibrogenesis, together with immune response activation in the graft. Thus, the gut microbiome can be considered a new therapeutic target for improving the longterm survival rates after liver transplantation (31).…”
Section: Introductionmentioning
confidence: 99%